Scar endometriosis following hysterotomy: a case report - K, Sasikala; Krishnamoorthy, Nivedita; KS, Shivaranjani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Scar endometriosis is a rare entity mostly following obstetrical and gynecological surgeries and difficult to diagnose. It is often misdiagnosed as abscess, suture granuloma or lipoma. We report a case of scar endometriosis following hysterotomy - because of its rarity.